2024
DOI: 10.1093/nsr/nwae108
|View full text |Cite
|
Sign up to set email alerts
|

An inorganic liquid crystalline dispersion with 2D ferroelectric moieties

Ziyang Huang,
Zehao Zhang,
Rongjie Zhang
et al.

Abstract: Electro-optical effect based liquid crystal devices have been extensively used in optical modulation techniques, in which the Kerr coefficient reflects the sensitivity of the liquid crystals and determines the strength of the device operational electric field. The Peterlin-Stuart theory and the O’Konski model jointly indicate that a giant Kerr coefficient could be obtained in a material with both a large geometrical anisotropy and an intrinsic polarization, but such a material is not yet reported. Here we reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This large Kerr coefficient will make it possible to build a large-scale, energy-efficient device. This work gives evidence of 2D ferroelectrics in layered silicates [90].…”
Section: D Vermiculitementioning
confidence: 53%
See 1 more Smart Citation
“…This large Kerr coefficient will make it possible to build a large-scale, energy-efficient device. This work gives evidence of 2D ferroelectrics in layered silicates [90].…”
Section: D Vermiculitementioning
confidence: 53%
“…These functional core layers then show excellent light response characteristics suitable for photocatalysis and optical applications. A very recent study has also shown that 2D VMT liquid crystalline dispersion prepared by a cationexchange method can show intrinsic ferroelectricity and a huge geometrical anisotropy factor over 1500, both of which contribute to the gigantic Kerr coefficient (about 3.0 × 10 −4 m V −2 ) [90]. This large Kerr coefficient will make it possible to build a large-scale, energy-efficient device.…”
Section: D Vermiculitementioning
confidence: 96%